Evaluation of discontinuation for adverse events of JAK inhibitors and bDMARDs in an international collaboration of rheumatoid arthritis registers (the ’JAK-pot’ study) - Aymon, R.; Mongin, D.; Bergstra, S. A.; Choquette, D.; Codreanu, C.; De Cock, D.; Dreyer, L.; Elkayam, O.; Huschek, D.; Hyrich, K. L.; Iannone, F.; Inanc, N.; et al. (Ann Rheum Dis, 2024)
BACKGROUND: In a clinical trial setting, patients with rheumatoid arthritis (RA) taking the Janus kinase inhibitor (JAKi) tofacitinib demonstrated higher adverse events rates compared with those taking the tumour necrosis factor inhibitors (TNFi) adalimumab or etanercept. OBJECTIVE: Compare treatment discontinuations for adverse events (AEs) among second-line therapies in an international real-world RA population. METHODS: Patients initiating JAKi, TNFi or a biological with another mode of action (OMA) from 17 registers participating in the ’JAK-pot’ collaboration were included. The primary outcome was the rate of treatment discontinuation due to AEs. We used unadjusted and adjusted cause-specific Cox proportional hazard models to compare treatment discontinuations for AEs among treatment groups by class, but also evaluating separately the specific type of JAKi. RESULTS: Of the 46 913 treatment courses included, 12 523 were JAKi (43% baricitinib, 40% tofacitinib, 15% upadacitinib, 2% filgotinib), 23 391 TNFi and 10 999 OMA. The adjusted cause-specific hazard rate of treatment discontinuation for AEs was similar for TNFi versus JAKi (1.00, 95% CI 0.92 to 1.10) and higher for OMA versus JAKi (1.11, 95% CI 1.01 to 1.23), lower with TNFi compared with tofacitinib (0.81, 95% CI 0.71 to 0.90), but higher for TNFi versus baricitinib (1.15, 95% CI 1.01 to 1.30) and lower for TNFi versus JAKi in patients 65 or older with at least one cardiovascular risk factor (0.79, 95% CI 0.65 to 0.97). CONCLUSION: While JAKi overall were not associated with more treatment discontinuations for AEs, subgroup analyses suggest varying patterns with specific JAKi, such as tofacitinib, compared with TNFi. However, these observations should be interpreted cautiously, given the observational study design.